2020
DOI: 10.1039/c9cs00676a
|View full text |Cite
|
Sign up to set email alerts
|

Formazanate coordination compounds: synthesis, reactivity, and applications

Abstract: Inorganic complexes of an emerging class of chelating N-donor ligands, formazanates, offer a unique combination of structurally tunable coordination modes, redox activity, and optoelectronic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 103 publications
0
72
0
3
Order By: Relevance
“…The fate of the [Pt(ppy)] + fragment that is lost during this reactioni sn ot known,b ut we did find, as depicted in Scheme 7, that product 9 could be prepared rationally and much more efficiently by simply treating Pt(DMSO) 2 Cl 2 with equimolar Fzb in refluxing acetonitrile, allowingt he diplatinum complext ob ei solated in a6 4% yield. Examining the structure in Figure 8, we note that the platinum centers are separated by al arge distance, 4.78 ,i ndicatingt hey are non-interacting, and we presume that the very downfield chemical shifti nt he 1 HNMR spectrum (13.70 ppm) is attributed to the protons at the 6-positions of the 2-pyridyl rings, which are in al ocked position that result in close approach (2.53 )t oN (3) and N(3A).…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 88%
See 1 more Smart Citation
“…The fate of the [Pt(ppy)] + fragment that is lost during this reactioni sn ot known,b ut we did find, as depicted in Scheme 7, that product 9 could be prepared rationally and much more efficiently by simply treating Pt(DMSO) 2 Cl 2 with equimolar Fzb in refluxing acetonitrile, allowingt he diplatinum complext ob ei solated in a6 4% yield. Examining the structure in Figure 8, we note that the platinum centers are separated by al arge distance, 4.78 ,i ndicatingt hey are non-interacting, and we presume that the very downfield chemical shifti nt he 1 HNMR spectrum (13.70 ppm) is attributed to the protons at the 6-positions of the 2-pyridyl rings, which are in al ocked position that result in close approach (2.53 )t oN (3) and N(3A).…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 88%
“…They are structurally related to b-diketiminates,b ut the two additional nitrogen atoms in the backbone provide formazanates with more accessible redox properties and stronger visible absorption, due to their more stabilized LUMOs. [1][2][3] Formazanates have garnered considerable attention in coordination chemistry due to their ligand-based redox processes, which may facilitate multielectron redox transformations, [4] bond activations [5] and excited-state charge separation. [6] Av ariety of formazanate complexes of many main-group metals [7][8][9][10][11][12][13][14][15][16] andf irst-and second-row transition metals [17][18][19][20][21][22][23] have been described.T hese studies demonstrate the versatile coordination chemistry of formazanate ligandsa nd provides ignificant insight into the opticala nd redox properties of these compounds.S ome coppercomplexesc an also mediate oxygen activation, [24,25] certain cobalt and iron complexes exhibit unique magnetic characteristics, [17,26] and boronc omplexes in many cases feature not only the tunable redoxp roperties but also visible to nearinfrared photoluminescence, [9][10][11][12][13] finding applicationsa sc ellimaging agents [27,28] and electrochemiluminescence emitters.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Besides, formazan complexes containing boron and different metals have been widely synthesized and their catalytic, optical, electrochemical and biological properties have been investigated in detail. [16][17][18][19][20] In our previous study, formazan derivative was utilized as electrochemical sensor for the modification of pencil graphite electrode for the detection of paracetamol. [21] Moreover, nitro-substituted formazan derivatives have been firstly reported by our group in colorimetric chemosensors application for recognition of fluoride anion.…”
Section: Introductionmentioning
confidence: 99%
“…Formazan/tetrazolium system is relatively useful in the determination of the effect of anti‐cancer drugs [14,15] . Besides, formazan complexes containing boron and different metals have been widely synthesized and their catalytic, optical, electrochemical and biological properties have been investigated in detail [16–20] . In our previous study, formazan derivative was utilized as electrochemical sensor for the modification of pencil graphite electrode for the detection of paracetamol [21] .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] Concurrent with our work, the Gilroy group [28][29][30][31][32][33][34][35][36][37] and others [38][39][40] have synthesized a variety of compounds with formazanate ligands, and studied their optical and electrochemical properties. 41 Previously, we described that main group (B and Al) complexes with these ligands can accept up to two electrons, and that these reduction products subsequently react with electrophiles (e.g., Bn + or H + ) to form new N-C and N-H bonds at the formazanate ligand (Scheme 1). [42][43][44][45] Furthermore, we have demonstrated that the [2e − /E + ]-equivalent 'stored' at the ligand could be converted to E • radicals via homolytic cleavage of the N-C (Bn) and N-H bonds, respectively.…”
Section: Introductionmentioning
confidence: 99%